Relationship between transactional, transformational leadership styles, emotional intelligence and job performance - Shahhosseini, Mohammad; Silong, Abu Daud; Ismail, Ismi Arif (ERM Publications, 2013)
Claims about the significant relationship or the positive influence of emotional intelligence on performance are numerous, in both the commercial and scientific literatures. However, despite the intense interest of the media and business consultants in the field of emotional intelligence or EI, and its increasingly popular use in organizations, there is little empirical evidence to support these claims. In this study, we investigated the relationships between EI, leadership styles among 192 managers. Emotional intelligence was evaluated employing the Schutte emotional intelligence scale and while the Bass and Avolve leadership styles scale was also adapted. Finally, job performance was measured by immediate managers. Results showed that emotional intelligence was positively correlated with emotion in job performance. Surprisingly, it also appears that transformational leadership style was correlated with job performance. These results suggest that emotional intelligence may provide an interesting new way of enhancing productivity through job performance.